The leading “blended” civil medical evacuation operation (MEDEVAC) in unforeseen health emergency. From military use to civil development - Nazzareno Fagoni; Giuseppe Stirparo; Giuseppe Maria Sechi; Andrea Comelli; Gabriele Perotti; Guido Francesco Villa; Alberto Zoli; Marco Botteri (Travel Medicine and Infectious Disease)
Introduction: Medical evacuation has historically been rooted in military contexts. It involves the systematic transfer of sick or injured individuals from the battlefield to designated medical facilities. Medical evacuation has found application in civilian settings: the Ebola outbreak and the COVID-19 pandemic. This paper examines the medical evacuation that occurred during the COVID-19 pandemic in Lombardy, Italy (Operation “MEDEVAC”), where overloaded hospitals required the transfer of patients to other regions and even internationally. Methods: MEDEVAC was implemented by the Regional Emergency and Urgency Agency (AREU). Data from MEDEVAC were analysed using the AREU register, detailing patient characteristics, transfer logistics, and outcomes. Results: From March to April 2020, 121 intensive care patients were transferred via MEDEVAC, primarily by air. 65 % of patients were moved to other Italian regions. The Federal Republic of Germany received 35 % of patients, all transported by air. Outcome and mortality rates among transferred patients were comparable to those within regional intensive care units. One life-threatening event was reported during transport. The return of patient to Lombardy showed a 100 % survival rate. Conclusion: This study emphasises the importance of standardised protocols, improved information exchange systems, and enhanced training for medical personnel involved in medical evacuation. MEDEVAC was found to be feasible and able to cope with demands that were excessive in relation to available resources. This study proposes the development of a shared protocol for air transport of patients and a model for international cooperation among emergency response agencies to optimise future medical evacuation activities in civil context.